Laparoscopic treatment of UPJ obstruction in ectopic pelvic kidneys in children (La Pediatria Medica e Chirurgica, 2012)
Aims: to assess the feasibility and safety of a laparoscopic approach to uPJ obstruction (uPJo) in ectopic pelvic kidneys. Material and Methods: in a retrospective analysis we selected 14 children, aged 6months to 17 years, 12 males, 2 females, who had been treated in our department between January 2004 and June 2011. 9 patients presented ureteropelvic junction obstruction (in 3 cases pelvic stones coexisted) with normal/moderately reduced (â‰¥25%) relative function at radionuclide scan (MAg3), 3 nonfunctioning kidneys associated or not to hypertension, 2 congenital hypo-dysplastic kidneys. the evaluation of each patient involved the medical history, ultrasound examination, VCug, MAg3 diuresis renogram and Mri in some cases. of the patients presenting uPJo, 5 underwent dismembered pyeloplasty with pyelolithotomy, if required, and 4 pelvic derotation with straightening of the uretero-pelvic junction. A previous cystoscopic placement of a double J stent was utilized. this facilitated the identification and dissection around the pelvis. With the patient in trendelenburg position we utilized an umbilical trocar and two trocar in the right and left iliac fossae; an additional trocar, when required, was inserted more cephalad on the midclavear line contralaterally to the lesion. the derotation of ureteropelvic junction was obtained by freeing the kidneyâ€™s lower pole and by placing intraperitoneally the junction protected with a double J stent. this was obtained by suturing the peritoneum behind the ureteropelvic junction resulting in a forward rotation of the major axis of the kidney and a straightening of the junction. the 5 patients presenting nonfunctioning ectopic kidneys underwent laparoscopic nephrectomy. While the removal of congenital hypoplasic kidneys resulted easy, the removal of nonfunctioning kidneys was more difficult due to their complex vascular situation and for the embryonic disposition. Results: the operating time varied between 40 to 200 minutes. no patient required conversion to open surgery. the hypertension resolved after nephrectomy in all cases. 2 cases of dismembered pyeloplasty required a placement of double J stent due the recurrence of symptoms and ! patient is waiting for redo operation. the pelvic derotation showed an improvement of diuretic MAg3 renogram and the function remained stable and patiens are symptoms-free. Conclusion: the uPJo in ectopic pelvic kidneys presents a large spectrum of presentation. the laparoscopic approach provides good surgical exposure, and operative times are acceptable compared to those of laparoscopic procedure in anatomically normal kidneys. it has also proved a very useful tool in the non-functioning kidney nephrectomy thank to the help of magnification in the identification of numerous aberrant vessels that are quite often found in the pelvic kidneys. the derotation of the pelvis seems a useful
Keywords: Ectopic; kidney; UPJ Obstruction